Effectiveness and Impact of Short Film Media in Interdisciplinary Project-Based Learning on the Development of Students' Social Skills and Characters - Anna Wawiyah; Nensy Megawati Simanjuntak; Sri Utami; Sarah Prather (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: One of the media that can be used in project-based learning involving several fields of study or interdisciplinary is short films. Among such strategies, project-based learning (PBL) has gained prominence for its ability to integrate knowledge across disciplines while cultivating critical life skills. This study explores the effectiveness and impact of incorporating short film media into interdisciplinary PBL to enhance students' social skills and character development.Aims: This study aims to explain the effectiveness of short film media as one of the means and infrastructure in learning. The existence of a project carried out by all class members with the theme of Indonesian culture gave birth to several extraordinary works.Methods: This research is a qualitative phenomenological type. Data collection techniques used are observation and interviews. The data analysis technique used is narrative. The data of this study are sentences, paragraphs, and data sources are words poured out by students during the observation process.Result: The results reveal that students engaged in short film-based PBL demonstrated significant improvement in teamwork, empathy, and moral reasoning, compared to those in conventional PBL settings. Furthermore, qualitative findings highlight increased student engagement and reflective thinking throughout the project.Conclusion: The study concludes that the integration of short films within interdisciplinary PBL serves as a powerful pedagogical tool to nurture socially responsible and emotionally intelligent learners.